Biodiversity of ruminant mycoplasmas in eastern Turkey: Application for vaccines and control strategies - Cetınkaya, Burhan; Karahan, Murat; Kalın, Recep; Atıl, Eray (My University, 2008)
-
01.01.2008
Keywords: Biyoloji; Mikrobiyoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji